2021
DOI: 10.52690/jswse.v2i2.247
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Principal Managerial Competence and School Facilities on Teacher Performance

Abstract: This study determined the effect of principal managerial competence and school facilities on teacher performance. This research is a quantitative study with a determination design using an ex post facto research design. The sample in this study was all teachers in SD Negeri in Sekayu District, Musi Banyuasin Regency, consisting of 97 teachers. The data collection techniques using questionnaires, documentation and observation. The data analysis technique used quantitative descriptive analysis techniques and mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Based on the conclusions above, school principals must have managerial skills and learning leadership and provide appropriate learning facilities to achieve school quality. This results in line with Darwansah et al (2021) which found that there is a significant influence jointly with the managerial competence of school principals and school facilities on the performance of the elementary school. As we know the performance of the teachers is one of the factors which contribute to the school quality.…”
Section: The Correlation Analysis Between School Quality and The Mana...supporting
confidence: 90%
See 1 more Smart Citation
“…Based on the conclusions above, school principals must have managerial skills and learning leadership and provide appropriate learning facilities to achieve school quality. This results in line with Darwansah et al (2021) which found that there is a significant influence jointly with the managerial competence of school principals and school facilities on the performance of the elementary school. As we know the performance of the teachers is one of the factors which contribute to the school quality.…”
Section: The Correlation Analysis Between School Quality and The Mana...supporting
confidence: 90%
“…"Many studies have concluded that school principals who focus on learning leadership produce better student achievement than those who focus less on learning leadership. Darwansah et al (2021) showed that there is a significant effect of school facilities on the performance of teachers. Additionally, there is a significant influence jointly with the managerial competence of school principals and school facilities on the performance of the elementary school.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to their inability to carry out their managerial responsibilities. The author uses a reference by Kartini et al (2020) and Qosumudin and Bunyamin (2020) the importance of principal leadership in achieving educational success, implying that the progress of a school is dependent on the principal's managerial position (Ulfathmi et al, 2021;Darwansah et al, 2021).…”
Section: Resultsmentioning
confidence: 99%